FOSTERING EDUCATIONAL INNOVATION THROUGH HUMAN-MACHINE PARTNERSHIP IN AI-BASED LEARNING SPACES - Izzatul Munawwaroh; Hasan Jali (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
This study aims to investigate how artificial intelligence (AI) drives educational innovation by enabling human-machine partnerships in AI-based learning environments. This study addresses a critical gap in the current literature, specifically the lack of empirical understanding of how AI transforms pedagogical strategies and enhances student engagement in faith-based educational institutions. Using a qualitative case study approach, this study was conducted in a Madrasah that has integrated AI technology into its teaching practices. Data were collected through semi-structured interviews, participant observation, and document analysis. Findings reveal that AI enables more personalized and data-driven teaching strategies by analyzing students’ learning patterns in real time. In addition, AI-powered teaching tools provide timely feedback and adaptive guidance, which accelerates students’ understanding processes. The study concludes that AI integration not only improves the quality of teaching and learning but also creates more inclusive and flexible learning spaces. Implications highlight the need for educational institutions to invest in teacher training and digital infrastructure to support sustainable and ethical human-machine partnerships in future learning systems.